THE ROLE OF THE NOTARY REGIONAL SUPERVISORY BOARD IN RESPONDING TO VIOLATIONS OF NOTARY DUTIES AND POSITIONS - Rastra Ananda; Rohaini Rohaini; Siti Nurhasanah; Sunaryo Sunaryo (Indonesia Private Law Review)
The Notary Supervisory Council (MPN) aims to enhance services and legal protection for the public utilizing notarial services. However, there has been an increase in irregularities committed by notaries, both administrative and material, impacting public trust. The imposition of sanctions by the MPN, particularly by the Regional Supervisory Council (MPW), is intended to address and deter violations. Between 2016 and 2020, there were 40 documented violations related to notarial duties and positions in Banten Province. During this period, the rate of violations exhibited inconsistent fluctuations. The effectiveness of sanctions imposed by the MPW has been suboptimal, as indicated by the inconsistent trends in violations. Several challenges impede MPW's supervisory role, including insufficient cooperation from notaries, a lack of engagement during examination sessions, and the heavy workload of MPW members. To address these issues, it is recommended that MPW implement regular socialization efforts to enhance notary professionalism, strengthen the relationship between notaries and the MPW, and conduct comprehensive internal, external, repressive, and preventive supervision.